2D layered transition metal dichalcogenides (MoS2): Synthesis, applications and theoretical aspects - Singh, A.K.; Kumar, P.; Late, D.J.; Kumar, A.; Patel, S.; Singh, J. (Applied Materials Today, 2018)
Recently, graphene and other two-dimensional (2D) transition metal dichalcogenides (TMDCs) have been widely explored due to their unique optical, mechanical, electrical and sensing properties for versatile electronic and optoelectronic applications. The atomically thin layers of TMDC materials have shown potential to replace state-of-the-art silicon-based technology. Graphene has already revealed an excess of new physics and multifaceted applications in several areas. Similarly, mono-layers of TMDCs such as molybdenum disulfide (MoS2) have also shown excellent electrical and optical properties possessing a direct band-gap of ∼1.8 eV combined with high mechanical flexibility. In contrast to semi-metallic graphene, the semiconducting behavior of MoS2 allows it to overcome the deficiencies of zero-band-gap graphene. This review summarizes the synthesis of 2D MoS2 by several techniques, i.e., mechanical and chemical exfoliation, RF-sputtering, atomic layer deposition (ALD) and chemical vapor deposition (CVD), etc. Furthermore, extensive studies based on potential applications of MoS2 such as the sensor, solar cells, field emission and as an efficient catalyst for hydrogen generation has been included. Theoretical aspects combined with the experimental observations to provide more insights on the dielectric, optical and topological behavior of MoS2 was highlighted.

Highly efficient field emission properties of radially aligned carbon nanotubes - Tripathi, P.; Gupta, B.K.; Bhatnagar, A; Patel, C.R.P; Banker, P.K.; Late, D.J.; More, M.A.; Lalla, N.P.; Phase, D.M.; Choudhary, R.J.; Shaz, M.A.; Ajayan, P.M.; et al. (Journal of Materials Chemistry C, 2018)
Here, we report extraordinary field emission properties from one pot synthesized aligned carbon nanotubes endowed with related Fe nanoparticles (NPs). The CNT configuration is in the form of a carbon hollow cylinder (CHC) with CNTs radially aligned towards the CHC axis. The structure generates electron field emission properties such as an ultralow turn on field (0.35 V μm−1 at 10 μA cm−2), a low threshold field (0.41 V μm−1 at 100 μA cm−2) and a high field emission current density (7.71 mA cm−2 at 0.78 V μm−1). It also exhibits multi-fold improvement in the field enhancement factor (1.34 × 104) with highly stable current emission at 100 μA measured for 14 h. No post synthesis treatment is required for enhanced field emission characteristics. The growth related Fe NPs assist in lowering the work function and hence enhancing the field emission properties. The possibility of assembling nano-structured field emitters into macroscale architectures suggests new prospects for next generation three dimensional electron sources.